2018
DOI: 10.1002/cbdv.201800134
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomicidal Activity of Dihydrobenzofuran Neolignans

Abstract: We have evaluated the antischistosomal activity of synthetic dihydrobenzofuran neolignans (DBNs) derived from (±)-trans-dehydrodicoumaric acid dimethyl ester (1) and (±)-trans-dehydrodiferulic acid dimethyl ester (2) against adult Schistosoma mansoni worms in vitro. Compound 4 ((±)-trans-4-O-acetyldehydrodiferulic acid dimethyl ester) displayed the most promising activity; at 200 μm, it kills 100 ± 0% of worms after 24 h, which resembles the result achieved with praziquantel (positive control) at 1.56 μm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Access to b-5 models with S-S substitution patterns is not possible due to the lack of af ree 5-position on the aromatic ring. However, b-5 Type Cm odels with H-H substitutionp atterns have been accessed via the general methods b-5 Method 1a [108,109] and b-5 Method1b [110] using methyl p-hydroxycinnamate as starting material. The synthesis of mixed G-Sm odelsh as also been accomplished using, for example, b-5 Method1ba nd am ixture of methyl ferulate (21)a nd methyl sinapate.…”
Section: B-5 Type Model Compoundsmentioning
confidence: 99%
“…Access to b-5 models with S-S substitution patterns is not possible due to the lack of af ree 5-position on the aromatic ring. However, b-5 Type Cm odels with H-H substitutionp atterns have been accessed via the general methods b-5 Method 1a [108,109] and b-5 Method1b [110] using methyl p-hydroxycinnamate as starting material. The synthesis of mixed G-Sm odelsh as also been accomplished using, for example, b-5 Method1ba nd am ixture of methyl ferulate (21)a nd methyl sinapate.…”
Section: B-5 Type Model Compoundsmentioning
confidence: 99%
“…The DBNs investigated in this study were synthesized as reported previously . Briefly, the core structure of compounds 1 to 8 was obtained by oxidative coupling of coumaric ( a ), ferulic ( b ), and caffeic ( c ) methyl esters promoted by Ag 2 O in acetone/benzene (5:8) mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Dihydrobenzofuran‐type neolignans (DBNs) and their correlated benzofuran‐type derivatives (BNs) are a group of NLs that display two phenylpropanoid units between positions 7‐O‐4′ and 8‐5′. Interest in DBN and BN skeletons stems from their wide spectrum of biological activities, such as trypanocidal, leishmanicidal, schistosomicidal, insecticidal, antioxidant, and anti‐inflammatory actions . The biological effects of synthetic and semisynthetic DBN derivatives have also been extensively investigated …”
Section: Introductionmentioning
confidence: 99%
“…Figure 1) were synthesized as previously reported. 2,6,7,16 All the chemical structures were confirmed by NMR analysis (see Supporting Information).…”
mentioning
confidence: 89%